Well-differentiated neuroendocrine carcinoma of the larynx: Confusion of terminology and uncertainty of early studies - Hunt, Jennifer L. (2020)
Well-differentiated neuroendocrine carcinoma (also known as "carcinoid") of the larynx is an exceedingly rare tumor that has an epithelial origin. These tumors are malignant and have a low, but definite, risk of metastasis. Although it can be challenging, this tumor should be differentiated from moderately differentiated neuroendocrine carcinoma (also known as "atypical carcinoid"). The clinical and pathologic features of this tumor, as well as treatment and prognosis, are reviewed in detail.